2005
DOI: 10.1007/s10014-005-0187-0
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic anatomy of the brain–meningioma interface

Abstract: We analyzed the relation between meningioma and the brain in 50 surgical cases. So-called capsule formation was seen in 20 meningiomas, of which 13 were categorized as thin and 7 as thick. In 21 meningiomas the arachnoid membrane was intact, and 10 meningiomas had no underlying arachnoid membrane. The other 19 tumors showed partial disruption of the arachnoid membrane. The degree of arachnoid disruption correlated with the tumor grade, perifocal edema, pial blood supply on angiography, and tumor size. The exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 20 publications
0
36
0
Order By: Relevance
“…27,34,45–47,50,65,67 Two studies found edema to be most common with convexity or parasagittal meningiomas, 11,38 but another did not observe a relationship to location, 29 and no consistent association between edema and tumor size or pathological subtype is present across studies. 11,29,38,49 Some groups have also suggested a relationship between brain invasion and edema, 39,44 although it is unclear if edema resulting from tumor infiltration differs from vasogenic edema in meningiomas without invasion. 31,39 Brain invasion was not investigated in our study, as these data were not reported in the source studies we examined.…”
Section: Discussionmentioning
confidence: 99%
“…27,34,45–47,50,65,67 Two studies found edema to be most common with convexity or parasagittal meningiomas, 11,38 but another did not observe a relationship to location, 29 and no consistent association between edema and tumor size or pathological subtype is present across studies. 11,29,38,49 Some groups have also suggested a relationship between brain invasion and edema, 39,44 although it is unclear if edema resulting from tumor infiltration differs from vasogenic edema in meningiomas without invasion. 31,39 Brain invasion was not investigated in our study, as these data were not reported in the source studies we examined.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive meningiomas disrupt structural integrity of the arachnoid and pia mater, which is followed by disintegration of the cortical layer and glial matrix [12][13][14]. It facilitates excretory-secretory phenomena with direct influence of the tumor metabolites on the adjacent brain parenchyma, results in development of pial vascular supply to the neoplasm, and alters blood-brain barrier permeability with typical formation of the vasogenic brain edema [15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…The biological role and functional contribution of MMPs is complex and their role in meningiomas is far from established. Previous studies have focused on establishing the role of MMP2 in meningiomas, in particular as it relates to tumor recurrence, brain invasion, and peritumoral edema, and the data is conflicting [10, 19, 21, 23, 24, 26, 2831, 48]. Though some studies found higher MMP2 expression levels in recurrent meningiomas [28, 48], others have found no association between meningioma grade and MMP2 levels [29].…”
Section: Discussionmentioning
confidence: 99%
“…Though some studies found higher MMP2 expression levels in recurrent meningiomas [28, 48], others have found no association between meningioma grade and MMP2 levels [29]. No correlation between MMP2 expression level and brain-invasive potential of meningiomas has been found to date [23, 24, 26]. Studies focused on the predictive potential of MMP2 on meningioma peritumoral edema have been contradictory, with Paek et al [30] suggesting a positive association, whereas Panagopolous et al [31] noted no such association.…”
Section: Discussionmentioning
confidence: 99%